How does the quality of leadership and mentoring relationships shape the ākonga experience in ITE programs? - Danielle Carter; Lindsey Wharekura (New Zealand Journal of Teachers' Work)
This teacher reflection explores how the quality of leadership and mentoring relationships shapes the ākonga (student) experience within Initial Teacher Education (ITE) programs, with a focus on the Bachelor of Early Childhood Education. Drawing from both managerial and lecturer perspectives, it examines how embodied and relational leadership practices, rooted in empathy, authenticity, and reflective dialogue, foster professional identity, resilience, and confidence in ākonga. The authors argue that effective mentoring is not confined to formal settings but often emerges through everyday interactions that create safe and inclusive spaces for growth. By modelling vulnerability and engaging in reciprocal relationships, leaders and lecturers support ākonga in bridging theory and practice, navigating classroom challenges, and developing a strong sense of belonging. The article concludes that leadership, when enacted with the whole self, becomes a transformative force that not only enhances learning outcomes but also inspires future educators to lead with integrity and connection throughout their professional journeys.